2007
DOI: 10.1136/adc.2006.097949
|View full text |Cite
|
Sign up to set email alerts
|

Frontal cerebral blood flow change associated with infant-directed speech

Abstract: IDS significantly increased brain function compared with ADS. These results suggest that the emotional tone of maternal utterances could have a role in activating the brains of neonates to attend to the utterances, even while sleeping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
73
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 15 publications
9
73
0
1
Order By: Relevance
“…Similarly, short direct projections between anterior temporal lobe and PFC that support auditory processing and speech perception (Romanski & Goldman-Rakic, 2002; Scott & Johnsrude, 2003) may also specialize relatively early to support language development. This prediction aligns with evidence showing increased PFC activation in infants when hearing infant-directed but not adult-directed speech (Saito et al, 2007), forward but not backward speech (Dehaene-Lambertz et al, 2002), and when organizing words by hierarchical contexts (Werchan et al, 2016). Other areas within the frontal lobe, such as the premotor area, may begin to specialize for control over more complex motor actions soon thereafter.…”
Section: Constraints On Adaptation and Niche Construction Via Anatomisupporting
confidence: 86%
“…Similarly, short direct projections between anterior temporal lobe and PFC that support auditory processing and speech perception (Romanski & Goldman-Rakic, 2002; Scott & Johnsrude, 2003) may also specialize relatively early to support language development. This prediction aligns with evidence showing increased PFC activation in infants when hearing infant-directed but not adult-directed speech (Saito et al, 2007), forward but not backward speech (Dehaene-Lambertz et al, 2002), and when organizing words by hierarchical contexts (Werchan et al, 2016). Other areas within the frontal lobe, such as the premotor area, may begin to specialize for control over more complex motor actions soon thereafter.…”
Section: Constraints On Adaptation and Niche Construction Via Anatomisupporting
confidence: 86%
“…In response to music, newborns' frontal lobe showed activation with increased [HbO 2 ] (Sakatani et al, 1999;Chen et al, 2002). Saito et al (2007a) found a larger increase in [HbO 2 ] in the frontal area in response to infant-directed speech than to adultdirected speech. Infant-directed speech tends to have richer prosodic expressions with exaggerated pitch contours, which is presumed to facilitate infants' speech acquisition.…”
Section: Frontal Activation In Response To Speechmentioning
confidence: 96%
“…Under normal conditions, oxygenation of the brain is determined by neuronal metabolic requirements and changes in neuronal activity are met by changes in perfusion [26][27][28][29] . At the same time, relative hypoxemia would be compensated by a hyperemic response and hyperoxia would be counteracted by arteriolar vasoconstriction, thus enabling a stable oxygen extraction [30][31][32] .…”
Section: Discussionmentioning
confidence: 99%